Studies of leaf surface of some Bursera Jacq. ex L. (Burseraceae) species and its taxonomic implications - Castro, Mercedes E.; Torrecilla, Pedro (Instituto de Ecología, A.C., 2013)
Leaf epidermis characteristics of six species of Bursera were studied using light and scanning electron microscopy (SEM). All species possess hypostomatic leaves, anomocytic stomata, and similar glandular and eglandular trichomes, with the exception of B. karsteniana which is glabrous. SEM of the leaf epidermis revealed that all have straight anticlinal walls, but these have a suite of sculptural characters unique to each species. Phenetic analyses separate the species into two groups, one formed by the three representatives of subgenus Bursera and the other by the three representatives of subgenus Elaphrium, supporting the aforementioned subdivision. Leaf epidermis features are taxonomically important for the genus.